2012
DOI: 10.1167/iovs.11-8186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment on the Rate of Visual Field Change in the Ocular Hypertension Treatment Study Observation Group

Abstract: PURPOSE. The goal in this study was to compare rates of visual field (VF) change before and after the initiation of treatment in participants originally randomized to the observation arm of the Ocular Hypertension Treatment Study (OHTS). METHODS.We included OHTS participants originally randomized to observation and excluded those who reached non-POAG endpoints. VF progression was determined using trend analysis. Global and localized rates of VF change were calculated based on linear regression over time of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
(21 reference statements)
2
34
0
1
Order By: Relevance
“…23 It should be noted that the mean follow-up duration (53.8±10.4 in GS and 48.3±11.8 in glaucoma) and the mean time to progression (53.3 ± 10.5 in GS and 47.1 ± 11.9 in glaucoma) were very close. This finding indicates that an average of 4 years of follow-up is required to observe visual-field progression using PLR in a treated glaucoma cohort, and we might have had found higher number of progressing eyes if these eyes were followed up for a longer period of time or if they were 24 Our results agree with a study conducted by Sung et al, 25 who demonstrated that an abnormal inferior optic disc or RNFL sector were associated with future visualfield progression. We found that lower baseline measures in the inferior optic nerve and RNFL are more likely to influence progressive glaucomatous visual-field loss.…”
Section: Discussionsupporting
confidence: 91%
“…23 It should be noted that the mean follow-up duration (53.8±10.4 in GS and 48.3±11.8 in glaucoma) and the mean time to progression (53.3 ± 10.5 in GS and 47.1 ± 11.9 in glaucoma) were very close. This finding indicates that an average of 4 years of follow-up is required to observe visual-field progression using PLR in a treated glaucoma cohort, and we might have had found higher number of progressing eyes if these eyes were followed up for a longer period of time or if they were 24 Our results agree with a study conducted by Sung et al, 25 who demonstrated that an abnormal inferior optic disc or RNFL sector were associated with future visualfield progression. We found that lower baseline measures in the inferior optic nerve and RNFL are more likely to influence progressive glaucomatous visual-field loss.…”
Section: Discussionsupporting
confidence: 91%
“…25 While the acute response is reasonably well established, it was important to determine whether there was a sustained elevation in extracellular ATP as many forms of glaucoma progresses over a time course of years. [44][45][46] Given that a loss of RGCs and an elevation of IOP were demonstrated in all three models used here, the increases in extracellular ATP likely result from a combination of mechanosensitive release and cell rupture.…”
Section: Discussionmentioning
confidence: 90%
“…Given that pathophysiological changes develop in many forms of glaucoma over the course of several years, [44][45][46] it is important to demonstrate that any putative mechanism linking elevation of IOP to disease also shows a sustained change. This study provides strong support that the changes in purinergic signaling are sustained throughout the period of IOP elevation.…”
Section: Physiological Implicationsmentioning
confidence: 99%
“…Criteria for overall change (i.e., for the entire visual field) have been based, arbitrarily, on fixed numbers of changing test locations, [8][9][10][11][12] and change at individual test locations has been defined with similarly arbitrary criteria of slope and associated P value. [8][9][10][11]13,14 In consequence, criteria for visual field change with PLR are not adapted to an individual patient's data. Rather, their specificity is likely to vary between patients, making results difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%